Protective behavioral strategies are more helpful for avoiding alcohol-related problems for college drinkers who drink less. Issue 5 (22nd June 2022) - Li, Xiaoyin; Clarke, Nickeisha; Kim, Su-Young; Ray, Anne E.; Walters, Scott T.; Mun, Eun-Young
Abstract: Objective: To examine race, gender, and alcohol use level as moderators of the association between protective behavioral strategies (PBS) and alcohol-related problems. Participants: A sample of 12, 011 participants who reported recent drinking (87.7% White, 61% Women) from Project INTEGRATE, a study that combined individual participant data (IPD) from 24 brief motivational intervention trials for college students. Methods: Hierarchical regressions were conducted to determine whether there was a moderated effect of PBS on alcohol problems across alcohol use levels, and whether the moderated protective effect of PBS by alcohol use differed by gender and race. Results: The protective association between PBS and alcohol-related problems was greater for those who drank less. This moderated effect did not differ across men and women or across racial groups. Conclusions: College drinking prevention programs should ensure that students are aware of the limits of PBS as a mitigator of alcohol problems.